2020
DOI: 10.1111/jcmm.16089
|View full text |Cite
|
Sign up to set email alerts
|

Circ_0075829 facilitates the progression of pancreatic carcinoma by sponging miR‐1287‐5p and activating LAMTOR3 signalling

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 38 publications
0
21
0
Order By: Relevance
“…Current evidence suggests that the CeRNA network composed of circRNA‐miRNA‐mRNA plays a key role in regulating carcinogenesis and development and regulates the biological characteristics of tumors. 18 Circ_0075829 has been found to regulate LAMTOR3 through the ceRNA network to promote pancreatic cancer progression, 7 suggesting that both ceRNA networks and noncoding RNAs (lncRNA, miRNA, and circRNA) can be further explored for cancer mechanisms based on LAMTOR3.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Current evidence suggests that the CeRNA network composed of circRNA‐miRNA‐mRNA plays a key role in regulating carcinogenesis and development and regulates the biological characteristics of tumors. 18 Circ_0075829 has been found to regulate LAMTOR3 through the ceRNA network to promote pancreatic cancer progression, 7 suggesting that both ceRNA networks and noncoding RNAs (lncRNA, miRNA, and circRNA) can be further explored for cancer mechanisms based on LAMTOR3.…”
Section: Discussionmentioning
confidence: 99%
“… 6 In addition, circ_0075829 has been found to promote pancreatic cancer progression through miR‐1287‐5P/LAMTOR3 signaling pathways. 7 In breast cancer research, miR‐20a could promote the apoptosis of breast cancer cells by regulating the MTOR signaling pathway via sponging LAMTOR3. 8 However, the expression and biological function of LAMTOR3 in KIRC remains unknown, warranting further exploration.…”
Section: Introductionmentioning
confidence: 99%
“…Hao et al confirmed that circ_0007534 can directly interact with miR-625 and miR-892b [73], which implied that circ_0007534/ miR-625/miR-892b regulation axis might contribute to the development of PDAC. circ_0013912, circ_0000069, circ_0071036, circ_0075829, circ_0099999 could also facilitate the proliferative, migratory and invasive rates of PaCa cells through sponging miR-7-5p, miR-144, miR-489, miR-1287-5p and miR-335-5p, respectively [74][75][76][77][78]. circSFMBT1 serves as a miR-330-5p sponge and also promotes PaCa growth and metastasis via regulating miR-330-5p/ PAK1 axis [79].…”
Section: Circrnas Play Key Roles In Pancreatic Cancermentioning
confidence: 99%
“…Numerous researches have shown that circRNAs can act as competitive endogenous RNAs (ceRNAs) by sponging miRNAs [ 10 ]. MiR-1287-5p functioned as a tumor inhibitor in various cancers, including breast cancer [ 11 ], colorectal cancer [ 12 ], and pancreatic carcinoma [ 13 ]. In non-small cell lung cancer (NSCLC), miR-1287 was proved to be sponged by circ_0016760 and circ_0026134 [ 14 , 15 ].…”
Section: Introductionmentioning
confidence: 99%